Closure to “Systemic Approach for the Capacity Expansion of Multisource Water-Supply Systems under Uncertainty” by João Vieira and Maria Cunha - Vieira, João (2017)
The authors acknowledge the publisher in granting permission for making post-print version available in open access institutional repository.